2021
DOI: 10.1039/d1tc01026c
|View full text |Cite
|
Sign up to set email alerts
|

Terbium(iii) bis-phthalocyaninato single-molecule magnet encapsulated in a single-walled carbon nanotube

Abstract: In this study, terbium(III) bis-phthalocyaninato single-molecule magnets (TbPc2 SMMs) were encapsulated in the internal nano space of single-walled carbon nanotubes (SWCNTs) for the first time. The magnetic and electronic properties...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…In 2021, Katoh et al first reported the encapsulation of Tb(Pc) 2 SMMs in the internal nanospace of SWCNTs ( Tb(Pc) 2 SMM@SWCNT ). 422 The magnetic and electronic properties of the Tb(Pc) 2 SMM@SWCNT hybrids (Fig. 35e) were investigated in detail using DC and AC magnetic susceptibility measurements, transition electron microscopy (TEM), scanning electron microscopy (SEM), STM, and STS.…”
Section: Development Of the Functionalities Of Sandwich Tetrapyrrole ...mentioning
confidence: 99%
“…In 2021, Katoh et al first reported the encapsulation of Tb(Pc) 2 SMMs in the internal nanospace of SWCNTs ( Tb(Pc) 2 SMM@SWCNT ). 422 The magnetic and electronic properties of the Tb(Pc) 2 SMM@SWCNT hybrids (Fig. 35e) were investigated in detail using DC and AC magnetic susceptibility measurements, transition electron microscopy (TEM), scanning electron microscopy (SEM), STM, and STS.…”
Section: Development Of the Functionalities Of Sandwich Tetrapyrrole ...mentioning
confidence: 99%
“…CASSCF methods and inclusion of spin–orbit (SO) coupling (CASSCF-SO calculations) were conducted with the ORCA 5.0.2 program 21 a using DKH-def2-SVP 21 b for all C atoms, DKH-def2-TZVP 7 for N and Sc atoms, SARC2-DKH-QZVP 21 c for Dy atoms and SARC-DKH-TZVP 21 d for Y atoms as the basis set. Seven orbitals localized on Dy with the shape of 4f orbitals were selected as active orbitals, and 21 of sextet states were mixed with the SO coupling.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, single-wall carbon nanotubes (SWCNTs) are good candidates for the construction of hybrid materials not only because of their high conductivities with long spin coherence times, 6 but also because of their uniform nanopores, which enable the encapsulation of molecules. 7 Supramolecular hybrid materials of Tb 3+ phthalocyaninato double-decker (TbPc 2 ) SMMs attached on the surface of SWCNTs are excellent spin valves, showing magnetoresistance ratios up to 300% at submillikelvin temperatures. 8 The extremely low operating temperatures are improved by encapsulation of SMMs into SWCNTs, wherein the magnitude of the interactions between SMMs and conduction electrons is enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental challenge is loss of magnetic anisotropy in the fabrication process due to loss of axial symmetry of the molecule, as a result of molecule–substrate interactions . The double-decker TbPc 2 possesses a large magnetic anisotropy along the principal molecular axis with a large U eff value of 514.3 cm –1 . , The engineered grafting of such double-decker SMM becomes facile due to π-conjugated macro-cyclic rings, retaining the uni-axial molecular symmetry intact. Apart from the unique structural feature and large U eff barrier, the exotic electronic structure makes TbPc 2 one of the most promising SMM contenders for technological applications. The sandwiched metallocenes, with a similar structure as of TbPc 2 , could also be suitable alternatives for SMMs . In this context, a series of sandwiched dysprosium metallocene complexes were synthesized by McClain et al, and a magnetic relaxation barrier up to 1468 cm –1 was achieved by modification in the molecular structure .…”
Section: Introductionmentioning
confidence: 99%